Evolution of Luyang Lake since the last 34, 000 years: Climatic changes and anthropogenic impacts. (10th June 2017) - Yan, Yonghao; Zhou, Jie; He, Zhong; Sun, Qianli; Fei, Jie; Zhou, Xinying; Zhao, Keliang; Yang, Linhai; Long, Hao; Zheng, Hongbo
Abstract: A sediment section retrieved from Luyang Lake, Shaanxi province, China was employed for grain-size, total organic carbon content (TOC) and carbonates (CaCO3 ) analyses. Based on the Optically Stimulated Luminescence (OSL) chronology, the evolution of Luyang Lake since the last 34, 000 years was reconstructed. Then the historical anthropogenic information like populations and arable lands obtained from literature were incorporated into the environmental sequence to demonstrate the linkage of lake evolution with both climatic and anthropogenic forcings. It indicated that the appearance of loessial sediment during ca. 33.4–10.7 ka exhibited a much lower lake level associated with a cold and dry climate setting. The sediment became finer with increasing TOC after ca. 10.7 ka implied the enhanced monsoon rainfall and relatively higher lake level until ca. 4.6 ka. Much higher TOC and lowest CaCO3 at 7.2–4.6 ka suggested the Holocene Climate Optimum in the region. The rising CaCO3 and declining TOC at ca. 4.6–2.0 ka revealed the enhanced evaporation/precipitation rate and depressed paleoproductivity, suggesting a drier climate. TOC reached its highest after ca. 2 ka, coinciding with the increasing population and the expanding arable lands since the last 600 years, would suggest the anthropogenic impacts like land reclamation and farming rather than climate forcing. Briefly, the evolution of Luyang Lake was controlled by the monsoon climate through geological times and the intensified anthropogenic interferences since the last 2 ka, especially the last 600 years, would account for the transformation of freshwater lake to a saline lake and wetland environment.